Austria : Recent Developments and Issues. (IMF Staff Country Reports; Country Report ;, 1995)
This report describes recent developments and issues in Austria. The report discusses the structural features of the Austrian labor market. Two features-the relative importance of foreign labor supply, and the comparatively low labor force participation of certain groups-are analyzed in detail. The historical structure of the Austrian balance of payments is discussed, and the developments in 1994 are analyzed. The report also examines the Austrian tourism industry and its underlying problems. Developments in public finances are also elaborated.